Aproximación al listado de plantas alóctonas invasoras reales y potenciales en España - Sanz Elorza, Mario; Dana, Elías; Sobrino, Eduardo (Lazaroa, 2001)
Gives the growing importance that invasions of alien plants are acquiring worldwide as a factor is environmental deterioration and loss of biodiversity, we present the checklist of invasive alien plants in Spain (Peninsula and Balearic Islands), similar to those already published in many other countries. The checklist is structured into two series covering plants with evident invasive behaviour (78 species) and those presenting invasive behaviour that is incipient or restricted to lowvalue ecosystems (currently90 species). By way of prevention, we also include the list of 56 species of invasive alien plants in northern Europe.